The Influence Of Food Quality Improvement Assistance On Increasing The Welfare Of People's Farmers - Ferdi Fathurohman; Nurul Mukminah; Wiwik Endah Rahayu; Hanik Atus Sangadah (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
Feed is a very important factor in the world of animal husbandry. Subang Regency is one of the beef cattle breeding centers in West Java and even in Indonesia and occupies the top 5 beef cattle populations in Indonesia. In Subang Regency, 1,500 families depend on beef cattle and other livestock businesses for their income, with an average of 3 to 4 livestock per family. but breeders in Subang Regency only focus on conventional livestock production processes and have not touched modern livestock. so that the level of welfare of farmers in Subang Regency is still not optimal. The biggest cost for livestock in Subang Regency is still the high price of concentrate and forage feed. This research aims to increase the knowledge of beef cattle breeders through counseling and coaching regarding the management of beef cattle in terms of improving the quality of feed so that it has added value. The research was carried out in Cibogo District, Subang Regency from July to November 2022 using the focus group discussion, training and monev methods. The results of this study are that the feed problem at the smallholder farmer level is the poor quality of the feed due to the lack of knowledge of breeders on how to process and store feed. Processing and storage are applied at the farmer level, namely storing forage fodder using the silage method and increasing knowledge of feed management. Breeders who are members of a group of beef cattle and are able to develop institutional management with standards for the production and management of feed in the group. There is a positive and significant influence between the provision of assistance in making feed on increasing the welfare of farmers.